A phase 2 trial of dacomitinib (PF‐00299804), an oral, irreversible pan‐HER (human epidermal growth factor receptor) inhibitor, in patients with advanced non–small cell lung cancer after failure of prior chemotherapy and erlotinib. Issue 8 (5th February 2014) - Reckamp, Karen L.; Giaccone, Giuseppe; Camidge, D. Ross; Gadgeel, Shirish M.; Khuri, Fadlo R.; Engelman, Jeff A.; Koczywas, Marianna; Rajan, Arun; Campbell, Alicyn K.; Gernhardt, Diana; Ruiz‐Garcia, Ana; Letrent, Stephen; et al.
<x xml:space="preserve">Abstract</x> BACKGROUND This phase 2 trial (ClinicalTrials.gov identifier NCT00548093) assessed the efficacy, safety, and impact on health‐related quality of life of dacomitinib (PF‐00299804), an irreversible tyrosine kinase inhibitor (TKI) of human epidermal growth factor receptors (EGFR)/HER1, HER2, and HER4, in patients with KRAS wild‐type non–small cell lung cancer (NSCLC). METHODS Patients with advanced NSCLC, progression on 1 or 2 regimens of chemotherapy and erlotinib, KRAS wild‐type or known EGFR‐sensitizing mutant tumor, and Eastern Cooperative Oncology Group performance status of 0 to 2 received 45 mg of dacomitinib once daily continuously in 21‐day cycles. RESULTS A total of 66 patients enrolled (adenocarcinoma, n = 50; those without adenocarcinoma [nonadenocarcinoma], n = 16). The objective response rate (ORR) for patients with adenocarcinoma (primary endpoint) was 5% (2 partial responses; 1‐sided P = .372 for null hypothesis [H0]: ORR ≤ 5%) and 6% (1 partial response) for patients with nonadenocarcinoma. Responders included: 2 of 25 EGFR mutation‐positive tumors; 1 of 3 EGFR wild‐type with HER2 amplification. Median progression‐free survival was 12 weeks overall (n = 66) and 18 weeks (n = 26) for patients with EGFR mutation‐positive tumors. Common treatment‐related adverse events were of grade 1 or 2 severity, manageable with standard supportive care, and included diarrhea (grade 3 [G3], 12%), acneiform dermatitis (G3, 6%), exfoliative rash (G3, 3%), dry skin (G3, 0%), fatigue (G3, 3%), and stomatitis (G3, 2%). Six patients (9%) discontinued due to treatment‐related adverse events. By patient report, NSCLC symptoms of dyspnea, cough, and pain (chest, arm/shoulder) showed improvement first observed after 3 weeks on therapy. CONCLUSIONS Dacomitinib demonstrated preliminary activity and acceptable tolerability in heavily pretreated patients, and may offer benefit in molecularly defined patient subsets. Cancer 2014;120:1145–1154. © 2014 The Authors. Cancer published by Wiley Periodicals, Inc. on behalf of American Cancer Society.